2013
DOI: 10.1093/aobpla/plt046
|View full text |Cite
|
Sign up to set email alerts
|

Fibre wall and lumen fractions drive wood density variation across 24 Australian angiosperms

Abstract: Wood density is often considered to be a key plant functional trait. But it is not clear what actually wood density is? We rigorously quantified anatomical underpinnings of wood density variation. We found that density was mainly driven by properties of mechanical tissue such as fibre wall fraction and fibre lumen fraction. However, there was also a substantial anatomical variation independent of density. This variation suggests that different plant ecological strategies may be available to woods with the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
154
3
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(185 citation statements)
references
References 60 publications
13
154
3
15
Order By: Relevance
“…Low-density wood is mechanically weaker [64][65][66][67][68][69][70] because a volume extension of wood requires fewer resources to construct [71], so it has been reported that wood density has a negative relationship with decomposition rate [72]. However, our results disagreed with previous studies regarding the relationship between mass loss and wood density, and indicated a positive relationship between the decomposition rate and wood density in both early and late stages of decomposition (Figure 3).…”
Section: Discussioncontrasting
confidence: 99%
“…Low-density wood is mechanically weaker [64][65][66][67][68][69][70] because a volume extension of wood requires fewer resources to construct [71], so it has been reported that wood density has a negative relationship with decomposition rate [72]. However, our results disagreed with previous studies regarding the relationship between mass loss and wood density, and indicated a positive relationship between the decomposition rate and wood density in both early and late stages of decomposition (Figure 3).…”
Section: Discussioncontrasting
confidence: 99%
“…The aforementioned numbers represent values typically encountered in wood (Fig. 8.1g ) (Von Frey-Wyssling and Aeberli 1942 ;Wagenführ 2007 ;Ruelle et al 2006 ;Zieminska et al 2013 ); however, more extreme values also occur. For example, very low ray proportions of around 7 % were reported for two Acacia species (Zieminska et al 2013 ), while very high axial parenchyma proportions of 67 % were measured in Ceiba aesculifolia ( Fig.…”
Section: How Much Ray and Axial Parenchyma Occurs In Wood?mentioning
confidence: 95%
“…Indeed, the fiber morphological properties of wood largely determine its density [37]. Higher fiber proportion and fiber wall thickness are associated with higher wood density [38,39]. On the other hand, a high percentage of vessel proportion will yield hydraulic conductivity, which could cause higher shrinkage, and a disruption in wood structure.…”
Section: Phenotypic Correlations Between Wood Propertiesmentioning
confidence: 99%